Mountain pastoralism in the Andes during colonial times - Gil Montero, Raquel (2009)
This article summarizes part of the history of the Andean herders during the colonial period. After the conquest, the Spaniards reorganized the American world in order to satisfy their primary needs: food, labor and transportation. During the silver boom of the late sixteenth and early seventeenth centuries, Potosí, the most important mining city in the Andes, surpassed 130,000 inhabitants, and there were many other settlements around smaller mining centres. All these urban inhabitants needed to be fed, and because of the location of these cities, food was often brought from distant places. This article shows how the pastoral peoples of the Andes managed to participate in, and adapt to, the colonial economy while at the same time retaining their pastoral way of life.